2013
DOI: 10.1155/2013/350815
|View full text |Cite
|
Sign up to set email alerts
|

Gross Morphological Features of the Organ Surface Primo-Vascular System Revealed by Hemacolor Staining

Abstract: The primo-vascular system (PVS), which consists of primo-vessels (PVs) and primo-nodes (PNs), is a novel thread-like structure identified in many animal species. Various observational methods have been used to clarify its anatomical properties. Here, we used Hemacolor staining to examine the gross morphology of organ-surface PVS in rats. We observed a sinus structure (20–50 μm) with a remarkably low cellularity within PNs and PVs and several lines of ductules (3–5 μm) filled with single cells or granules (~1 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 29 publications
5
26
0
Order By: Relevance
“…The PVS tissue has been identified in various sites, such as internal organs [ 4 7 ], brain ventricles [ 8 ], and blood and lymphatic vessels [ 9 – 11 ] in several animal species [ 12 ]. Various techniques have been used to visualize the PVS, including trypan blue, through which many important anatomical features of the PVS have been elucidated [ 2 ], and Hemacolor utilized in recent research [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PVS tissue has been identified in various sites, such as internal organs [ 4 7 ], brain ventricles [ 8 ], and blood and lymphatic vessels [ 9 – 11 ] in several animal species [ 12 ]. Various techniques have been used to visualize the PVS, including trypan blue, through which many important anatomical features of the PVS have been elucidated [ 2 ], and Hemacolor utilized in recent research [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, rod-shaped nuclei (revealed by DNA-specific staining) are linearly aligned along the longitudinal axis of the PVS [ 5 , 9 , 11 ]. Third, the PVS contains various immune cells, including mast cells (MCs) and white blood cells (WBCs), such as eosinophils, neutrophils, and lymphocytes, and it has a unique cellular composition [ 6 , 13 , 14 ] and a high number of MCs and WBCs. Fourth, the PVS is composed of a bundle of several small subducts or ductules (10–50 μ m) containing immune cells [ 6 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lim et al 2 suggested that the rat organ-surface primo vessel can be useful in identifying the primo tissues by morphologically observing with Hemacolor staining followed by simple light microscope for a brief time.…”
Section: Introductionmentioning
confidence: 99%
“…24 Innate immune cells, especially mast cells, have been found to be highly concentrated in the PVS, suggesting that it has an immune function. [25][26][27] In addition, hematopoietic stem cells 28 and small embryonic-like stem cells 29,30 have been observed in the PVS, suggesting that it has a regenerative function.…”
Section: Introduction Smentioning
confidence: 99%